Results of an evaluation study of induction and mentoring for beginning special education teachers: what do they need? - Sebald, Ann M.; Rude, Harvey A. (Social Welfare: Interdisciplinary Approach, 2015)
This study reviews the results from a three-year evaluation study of one local school district’s induction and mentoring program for beginning special education teachers in the United States. Data were collected for two years, with an intervention implemented in year three. Results indicate that through strategic and intentional support, the district improved how it supported this unique group of novice professionals. Designing induction and mentoring programs with the intent to maintain and foster the professional development of beginning teachers has implications for supporting the district’s intellectual capital in developing feelings of efficacy in teaching. Connecting induction and mentoring support with teacher preparation programs is discussed as a promising strategy to develop more systematic efforts in these areas. The essential skills for successful mentor teachers in support of learning focused relationships are identified.